2011
DOI: 10.1002/smll.201001640
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled Carbon‐Nanotube‐Functionalized Microelectrode Arrays Fabricated by Microcontact Printing: Platform for Studying Chemical and Electrical Neuronal Signaling

Abstract: A facile method is proposed for the deposition of multiwalled carbon nanotube (MWCNT) layers onto microelectrode arrays by means of a microcontact printing technique, leading to the fabrication of MEAs characterized by well defined electrical and morphological properties. Using polydimethyl siloxane stamps, produced from different mold designs, a flexibility of printing is achieved that provides access to microscale, nanostructured electrodes. The thickness of MWCNT layers can be exactly predetermined by evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 31 publications
0
25
0
2
Order By: Relevance
“…[29] In another study, Prato and co-workers used the micro-contact printing technique to deposit functionalized MWCNTs onto arrays of titanium nitride (TiN), creating CNT microelectrode arrays with well-defined electrical and morphological properties. [291] To accomplish this task, polydimethylsiloxane (PDMS) stamps produced from microfabricated molds were used to transfer MWCNT films (Figure 11g and 11h). They showed that functionalized MWCNT microelectrodes exhibit electrochemical and structural properties favorable for both neural recording and electrochemical detection of neurotransmitters, such as dopamine.…”
Section: Electroactive Nanomaterials For Electrode-tissue Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] In another study, Prato and co-workers used the micro-contact printing technique to deposit functionalized MWCNTs onto arrays of titanium nitride (TiN), creating CNT microelectrode arrays with well-defined electrical and morphological properties. [291] To accomplish this task, polydimethylsiloxane (PDMS) stamps produced from microfabricated molds were used to transfer MWCNT films (Figure 11g and 11h). They showed that functionalized MWCNT microelectrodes exhibit electrochemical and structural properties favorable for both neural recording and electrochemical detection of neurotransmitters, such as dopamine.…”
Section: Electroactive Nanomaterials For Electrode-tissue Interfacesmentioning
confidence: 99%
“…In addition, electrophysiological measurements from cultured hippocampal neurons showed that MWCNT microelectrodes had recording properties superior to those of commercial TiN microelectrodes under long-term cell-culture conditions (Figure 11i–k). [291] …”
Section: Electroactive Nanomaterials For Electrode-tissue Interfacesmentioning
confidence: 99%
“…Deposition of CNTs onto TiN microelectrode arrays was proposed by means of a micro-contact printing technique by Fuchsberger and colleagues [114], and showed superior recording properties compared to commercial TiN microelectrodes. The same microelectrodes were also employed to electrically stimulate and record neuronal activity, as well as to detect low concentrated amounts of dopamine.…”
Section: Reviewmentioning
confidence: 99%
“…Although there have been continuous efforts to increase the spatial resolution of neural recording by reducing the size of the conventional electrodes, it is difficult to avoid the deterioration of their mechanical strength and electrical conductivity, which are important for implanting the electrode and collecting neural signal, respectively. Recently, nanomaterials such as carbon nanotubes, silicon nanowires, or gold nanoparticles were employed to fabricate neural electrodes, allowing the successful miniaturization of the electrode without sacrificing material properties [15,[51][52][53][54][55][56][57][58][59][60][61] . Single-crystalline Au NWs possessing superflexibility as well as superstrength, high electrical conductivity, and well-defined geometry with sharp tip can potentially be ideal neural electrode materials.…”
Section: Nanoprobe For Neural Recordingmentioning
confidence: 99%